Experiences in information and communication technology applied in education A conceptual analytical approach in spaces and some performance Students of Education Sciences at the University of Msila - boutera, brahim; boutera, yousra (Journal of Social Sciences and Humanities, 2021)
ICTs have taken a prominent place in pedagogical practices and discussions, and forums; This requires a certain awareness of terminology, a clarification of conceptual frameworks (a pedagogical watch) on the practical and theoretical levels, to be able to be informed, and make the most of experiences, (knowledge and know-how) know how to make decisions, to properly manage our educational spaces, and the educational processes in our schools and universities, and to create and innovate in our educational policies; The latter through multiple efforts aim at establishing the rules of pedagogical quality within educational and teaching structures, digitizing, integrating technologies. This intervention presents a conceptual analytical approach, and clarifies a comparison on the issue, gives remarks and observations on performance, outline issues, within the framework to provide some key ideas for a better change, focus on the issue of terminology and the university culture, in this era of technologies applied to the fields of education and training. The researchers used a descriptive analytical approach and an observation and analysis grid of the work done by the students. It turns out that we need more efforts to digitize educational spaces. The product of the university is out of competition.